Evaluating activities of daily living using an infrared depth sensor: KINECTTM. - Kusunoki, Masanobu; Kohama, Takeshi; Yamada, Yoshifumi; Fujita, Eiji; Okada, Soichi; Maeda, Akira; Takeshima, Nobuo (Disability & Rehabilitation: Assistive Technology, 2019)
Purpose: With a growing proportion of elderly people in the population, the maintenance of activities of daily living (ADLs) in elderly people is crucial to keep medical costs down. We investigated the ADL measurement accuracy of KINECTTM and Kinect Studio. To eliminate the subjectivity of conventional methods, we numerically assessed motions with computer analysis. Methods: Eighteen actions that repeated "move" and "stationary" phases, including movement of arms, legs, head and torso were measured using KINECTTM. Errors and standard deviations of joint coordinates at the stationary points outputted from KINECT Studio were evaluated. Simultaneous measurements were performed with KINECTTM using conventional high-performance motion capture, and the output was treated as a true value for comparison. Results: In most motions, errors of the joint coordinates were within 100 mm; however, there were two cases where errors due to the skeleton-model estimation by KINECT Studio increased. Firstly, when a part of the body unexpectedly moved out of the infrared measurable area, and secondly, when parts of the body overlapped each other on the KINECTTM image. Conclusions: KINECTTM and Kinect Studio are effective for ADL assessment when positions that cause large errors are excluded. Since KINECTTM has sufficient precision, it should also be possible to develop a more appropriate ADL evaluation system with a new algorithm of skeleton-model estimation that does not depend on KINECT Studio. The KINECTTM and Kinect Studio are effective for ADL assessment when positions that cause large errors are excluded With an increasing proportion of elderly people in the population, the maintenance of activities of daily living (ADLs) in elderly people is crucial to keep medical costs down Systems such as the KINECTTM can support these goals